Target sequence data shed new light on the infrafamilial classification of Araceae. Issue 2 (5th February 2023) - Haigh, Anna L.; Gibernau, Marc; Maurin, Olivier; Bailey, Paul; Carlsen, Mónica M.; Hay, Alistair; Leempoel, Kevin; McGinnie, Catherine; Mayo, Simon; Morris, Sarah; Pérez‐Escobar, Oscar Alejandro; Yeng, Wong Sin; et al.
Abstract: Premise: Recent phylogenetic studies of the Araceae have confirmed the position of the duckweeds nested within the aroids, and the monophyly of a clade containing all the unisexual flowered aroids plus the bisexual‐flowered Calla palustris . The main objective of the present study was to better resolve the deep phylogenetic relationships among the main lineages within the family, particularly the relationships between the eight currently recognized subfamilies. We also aimed to confirm the phylogenetic position of the enigmatic genus Calla in relation to the long‐debated evolutionary transition between bisexual and unisexual flowers in the family. Methods: Nuclear DNA sequence data were generated for 128 species across 111 genera (78%) of Araceae using target sequence capture and the Angiosperms 353 universal probe set. Results: The phylogenomic data confirmed the monophyly of the eight Araceae subfamilies, but the phylogenetic position of subfamily Lasioideae remains uncertain. The genus Calla is included in subfamily Aroideae, which has also been expanded to include Zamioculcadoideae. The tribe Aglaonemateae is newly defined to include the genera Aglaonema and Boycea . Conclusions: Our results strongly suggest that new research on African genera ( Callopsis, Nephthytis, and Anubias ) and Calla will be important for understanding the early evolution of the Aroideae. Also of particular interest are the phylogenetic positions of the isolated genera Montrichardia, Zantedeschia, and Anchomanes, which remain only moderately supported here.